Prediction of the Individual Risk of Bronchial Obstruction in Acute Bronchitis in Infants - O.Ye. Abaturov; O.O. Rusakova (Zaslavsky O.Yu., 2015)
The objective of the study was to determine highly informative clinical-anamnestic, immunological and molecular-genetic risk factors of bronchial obstruction in acute bronchitis in infants. Methods. We have evaluated the content of IFN-γ, IL-4 and IL-13 in blood serum using enzyme-linked immunosorbent assay, the concentration of total IgE - using electrochemiluminescence immunoassay. The level of the transcription factor NF-κB expression in peripheral blood lymphocytes was studied by flow cytometry. Results. We have examined 80 children aged from 6 months to 3 years with acute obstructive bronchitis, and 40 age-matched children with acute nonobstructive bronchitis. The factors of high risk were determined and the mathematical model for predicting bronchial obstruction in acute bronchitis was created. Father's age over 38 years, intrauterine growth restriction, maladjustment syndrome, early artificial feeding, genetic predisposition to atopy, passive smoking, fever in the postvaccination period, history of acute obstructive bronchitis and number of its episodes more than 2, paratrophia became prognostically significant. Fever up to 37.7 °C, mild intoxication syndrome up to 3 days, slow nasal breathing, IL-13 within 4.05-6.71 pg/ml and the relative number of lymphocytes expressing NF-kB less than 49.8 % were also associated with the development of bronchial obstruction in acute bronchitis.